Grid-Ordering for Outlier Detection in Massive Data Streams - V. Sánchez Vinces, Braulio; Robson L. F. Cordeiro (Journal of Information and Data Management, 2025)
Outlier detection is critical in data mining, encompassing the revelation of hidden insights or identification of potentially disruptive anomalies. While numerous strategies have been proposed for serial-processing outlier detection, the ever-expanding realm of big data applications demands efficient distributed computing solutions. This paper addresses the challenge of real-time outlier detection in multidimensional data streams with high-frequency arrivals, by presenting GOOST. This novel algorithm employs neighborhood analysis by leveraging grid-based data sorting. GOOST efficiently detects distance-based outliers, ensuring accurate detection in distributed environments within a competitive and much more stable processing time than previous solutions. We perform experiments on 6 real and synthetic data sets with up to 1.2M events, and up to 55 dimensions. We demonstrate that GOOST outperforms 3 state-of-the-art methods in terms of quality of results (30% more accurate) within competitive (and 45% more stable) processing times for real-time analysis of multidimensional data streams and high event frequency, thus offering a promising solution for various scientific and commercial domains.